2020
DOI: 10.1016/j.oraloncology.2020.104885
|View full text |Cite
|
Sign up to set email alerts
|

Use of artificial intelligence in diagnosis of head and neck precancerous and cancerous lesions: A systematic review

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 48 publications
0
99
0
3
Order By: Relevance
“…AI and computerized support, although not new to healthcare, have lately received a lot of attention within the sphere of dentistry. These reviews covered their potential dental applications [ 19 ], success in detecting precancerous lesions and metastases [ 20 ], effectiveness in improving the quality of maxillofacial radiology [ 21 ], success in orthodontic treatment [ 22 ], and orthopedic rehabilitation [ 23 ], as well as concurrent application with virtual reality to decrease anxiety in young patients [ 24 ]. However, the aforementioned reviews did not systematically explore the current diagnostic capabilities of AI in identifying common orofacial diseases and disorders and/or the subsequently elicited pain [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…AI and computerized support, although not new to healthcare, have lately received a lot of attention within the sphere of dentistry. These reviews covered their potential dental applications [ 19 ], success in detecting precancerous lesions and metastases [ 20 ], effectiveness in improving the quality of maxillofacial radiology [ 21 ], success in orthodontic treatment [ 22 ], and orthopedic rehabilitation [ 23 ], as well as concurrent application with virtual reality to decrease anxiety in young patients [ 24 ]. However, the aforementioned reviews did not systematically explore the current diagnostic capabilities of AI in identifying common orofacial diseases and disorders and/or the subsequently elicited pain [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the reference standard should include multiple annotations from different experts to reduce subjectivity and account for interobserver variability. 23 This is particularly important in the context of AI given its potential capabilities in detecting disease more accurately than human operators. 1 Furthermore, AI may also be capable of detecting subtle changes indicative of a diagnosis through recognition of patterns not detectable by human operators, for example deriving cardiovascular risk from retinal images, identification of individuals with atrial fibrillation from their ECGs taken during sinus rhythm and identifying stromal features associated with breast cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…13 studies reported an inability to provide systematic quality assessment or evaluate certain biases as a limitation in their study (Supplementary Table 2). Specifically, these included concerns around size and quality of the dataset, including its real-world clinical applicability; for example including a whole tissue section instead of a portion of interest only 23 and providing samples from multiple centres across different demographic populations to improve generalisability of the model. Appropriate separation of data set into training, validation and test sets without overlap was also highlighted as an area needing evaluation, as overlap between datasets would lead to higher accuracy rates.…”
Section: Patient Selection -Photographicmentioning
confidence: 99%
“…In addition to several functional symptoms like teeth loss, head-neck pain and potentially fatal consequences, this craniofacial disease also likely results in disfigurement of patients without early diagnosis or favorable prognosis. Classical oral cancer detection and diagnosis are based on radiological analysis, clinical monitoring indicators and histopathological assessments ( Mahmood et al, 2020 ). Prevention and early-stage diagnosis are of great significance to the survival rate and treatment management of cancerous patients.…”
Section: Applications Of ML In the Dental Oral And Craniofacial Imaging Fieldmentioning
confidence: 99%
“…Semantic image segmentation and feature extraction are two fundamental processes of image classification through ML methods. They form the basis of oral cancer detection by this type of approach ( Haider et al, 2020 ; Mahmood et al, 2020 ). Hyperspectral Imaging (HSI) is a currently applicable technique for tumor detection.…”
Section: Applications Of ML In the Dental Oral And Craniofacial Imaging Fieldmentioning
confidence: 99%